RELATIONSHIP BETWEEN THE STUDENTS' FUNCTIONAL STATUS OF ORGANISM, BODY COMPOSITION AND HEALTH SELF-ASSESSMENT - Vecenāne, Helēna; Fernāte, Andra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The person’s physical and mental health is a topical issue nowadays, as often it is believed that all the responsibility for person’s health must be in the hands of the state health care institutions. Educating society on health issues in various levels is very perspective, especially important it is at the educational establishments. If the education on health related issues is continuously taking place in comprehensive educational establishments, insufficient attention is paid to it in the higher educational establishments. The aim of the research is to define the correlations between the functional state of the organism, body composition and health assessment of students of Liepaja University and Riga Stradins University Liepaja Branch. The research results proved that the correlation between the students` functional condition of organism, body composition and health self- assessment can be evaluated as weak. A significant correlation between the students' functional condition of organism and body composition was not found.